2019
DOI: 10.1136/annrheumdis-2019-216128
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in biologic users for rheumatic diseases: results from the South African Biologics Registry (SABIO)

Abstract: ObjectivesTo evaluate the rate of tuberculosis (TB) in biologic users for rheumatic diseases in South Africa, the effectiveness of our latent TB infection (LTBI) programme, risk factors and outcome.MethodsTB cases were collected from the South African Biologics Registry (SABIO), rheumatologists and pharmaceutical companies. Demographics, LTBI screening and treatment, biological and disease modifying antirheumatic drug (DMARD) therapies, TB diagnosis and outcomes were recorded.Results96 TB cases were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The introduction of TNFi in clinical practice led to a significant increase in cases of tuberculosis (TB) reactivation in patients with an undiagnosed, underlying latent TB infection (LTBI). 38 Although TB reactivation was mainly associated with TNFi, TB cases have been reported at a lower rate with other bDMARDs 39 , 40 and tsDMARDs. 22 However, the universal screening of patients prior to bDMARD initiation with the tuberculin skin test (TST) and/or the newer Interferon Gamma Release Assays (IGRAs), have led to a substantial decrease of newly diagnosed TB cases (∼80%).…”
Section: Opportunistic Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of TNFi in clinical practice led to a significant increase in cases of tuberculosis (TB) reactivation in patients with an undiagnosed, underlying latent TB infection (LTBI). 38 Although TB reactivation was mainly associated with TNFi, TB cases have been reported at a lower rate with other bDMARDs 39 , 40 and tsDMARDs. 22 However, the universal screening of patients prior to bDMARD initiation with the tuberculin skin test (TST) and/or the newer Interferon Gamma Release Assays (IGRAs), have led to a substantial decrease of newly diagnosed TB cases (∼80%).…”
Section: Opportunistic Infectionsmentioning
confidence: 99%
“…Despite appropriate baseline screening, cases of TB continue to be diagnosed worldwide during long term b- or ts-DMARD therapy. 39 , 40 These cases are thought to be mainly due to TB re-exposure rather than reactivation. In the long-term extension studies of RCTs in RA patients treated with TNFi, 48 non-TNFi 49 bDMARDs or ts-DMARDs 22 , the incidence rate of TB ranged between 0.1 to 0.2/100 patient-years.…”
Section: Opportunistic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated the incidence of TB disease in public health sector patients exposed to biologic therapies in South Africa, Western Cape. We found that the estimated incidence rate among biologic therapy users was higher compared to previously published literature [22,24]. When comparing estimated tuberculosis disease incidence rates to the estimated background incidence rate of 681 cases per 100,000 per year in the Western Cape [25], the estimated risk of tuberculosis disease is 3.3 fold higher overall, and is 4.1-fold and 2.7-fold higher than background incidence rates in TNF-α and non-TNF-α biologic therapies respectively.…”
Section: Discussionmentioning
confidence: 51%
“…The South African Biologics Registry (SABIO) captures biologic use data for South African patients receiving private health care, but these are generally individuals with higher socio-economic circumstances and lower risk of exposure to TB, and are not representative of the general South African patient population. When comparing the TB incidence rates in TNF-α inhibitors users in the SABIO registry, incidence was 1387 per 100,000 person-years, which is approximately 10-fold that of the British (BSRBR), French (RATIO) and Spanish (BIOBADASER) registries where the TB incidence ranges from 106 to 172 per 100,000 person-years [22,24].…”
Section: Introductionmentioning
confidence: 98%